A look at the evolution of the academic spin-offs creation in Iberoamerican countries: the cases of Spain and Colombia - Morales-Gualdrón, Silvia Teresa (2020)
The research based companies creation ‒academic spin-offs‒ is a phenomenon that has been consolidated in developed countries, such as the United States, France, the United Kingdom and Israel; nevertheless, this kind of companies appeared recently in Ibero-American countries.  This article presents an analysis on the development of academic spin-offs in two Ibero-American countries, Spain and Colombia. Some critical aspects were analyzed: R & D investment, regulatory framework, availability of financial resources, and support infrastructure for firm creation. The results highlight a greater development in the Spanish case than in the Colombian one but, in both cases, the institutional competences for research and development of the universities’ capacities have been strengthened, some legal barriers for public employees and universities’ shareholder participation have been eliminated, and a support ecosystem for technology-based entrepreneurship has been consolidated, which will favor academic spin-off processes in the future.